Improving the quality of maternal and newborn care in the Pacific region: A scoping review - A.N. Wilson; N. Spotswood; G.S. Hayman; J.P. Vogel; J. Narasia; A. Elijah; C. Morgan; A. Morgan; J. Beeson; C.S.E. Homer (Elsevier, 2020)
Background: Quality care is essential for improving maternal and newborn health. Low- and middle-income Pacific Island nations face challenges in delivering quality maternal and newborn care. The aim of this review was to identify all published studies of interventions which sought to improve the quality of maternal and newborn care in Pacific low-and middle-income countries. Methods: A scoping review framework was used. Databases and grey literature were searched for studies published between January 2000 and July 2019 which described actions to improve the quality of maternal and newborn care in Pacific low- and middle-income countries. Interventions were categorised using a four-level health system framework and the WHO quality of maternal and newborn care standards. An expert advisory group of Pacific Islander clinicians and researchers provided guidance throughout the review process. Results: 2010 citations were identified and 32 studies included. Most interventions focused on the clinical service or organisational level, such as healthcare worker training, audit processes and improvements to infrastructure. Few addressed patient experiences or system-wide improvements. Enablers to improving quality care included community engagement, collaborative partnerships, adequate staff education and training and alignment with local priorities. Conclusions: There are several quality improvement initiatives in low- and middle-income Pacific Island nations, most at the point of health service delivery. To effectively strengthen quality maternal and newborn care in this region, efforts must broaden to improve health system leadership, deliver sustaining education programs and encompass learnings from women and their communities.